2018
DOI: 10.1155/2018/7849675
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Predictors of Plasma Levels of Soluble RAGE in Critically Ill Patients: Secondary Analysis of a Prospective Multicenter Observational Study

Abstract: Rationale Although soluble forms of the receptor for advanced glycation end products (RAGE) have been recently proposed as biomarkers in multiple acute or chronic diseases, few studies evaluated the influence of usual clinical and biological parameters, or of patient characteristics and comorbidities, on circulating levels of soluble RAGE in the intensive care unit (ICU) setting. Objectives To determine, among clinical and biological parameters that are usually recorded upon ICU admission, which variables, if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…In spite of the AGE‐RAGE axis playing a direct role in immune cell recruitment, adhesion, and differentiation during the acute inflammatory response, 19 this study found no relationship between peripheral blood WCC and sRAGE levels, in accordance with the literature 27,33 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In spite of the AGE‐RAGE axis playing a direct role in immune cell recruitment, adhesion, and differentiation during the acute inflammatory response, 19 this study found no relationship between peripheral blood WCC and sRAGE levels, in accordance with the literature 27,33 …”
Section: Discussionsupporting
confidence: 89%
“…Both Mauri et al 34 and Wiegers et al 35 described the changes in biomarkers levels overtime after an inflammatory insult: sRAGE increased earlier than CRP (or PCT) and then decreased quickly and consistently. This could be the reason why sRAGE levels show no correlation with CRP or PCT when determined on the first 24 hours of admission 15,27 and, on the other hand, show a positive correlation when measured after 72 hours or at different time points, like in our study 36 …”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…In addition to the normal role of RAGE associated with innate immunity, it can also orchestrate cellular proliferation and differentiation [ 27 ]. Thus, increases in the RAGE ligands have also been implicated in a range of disease states, such as Alzheimer’s Disease, diabetes, and during tumor growth [ 19 , 28 , 29 ].…”
Section: The Receptor For Advanced Glycation End Productsmentioning
confidence: 99%
“…There is no clear evidence of the etiopathogenic mechanisms of HPV infection. Multiple factors contributing to its pathogenesis have been suggested, such as the lack of efficient protective cell mechanisms against the virus and the accumulation of toxic compounds which induce oxidative stress and inflammation [14,15,16,17,18,19]. Oxidative stress and inflammation are two interconnected processes which produce multiple effects on cell function [20].…”
Section: Introductionmentioning
confidence: 99%